Could application of epinephrine improve hemostatic efficacy of hemoclips for bleeding peptic ulcers? A prospective randomized study - Grgov Saša; Radovanović-Dinić Biljana; Tasić Tomislav (Vojnosanitetski Pregled)
Background/Aim. Bleeding from peptic ulcers can be effectively and safely treated with endoscopic hemoclips therapy. However, due to certain limiting factors of hemoclips, application of combination with another endoscopic method may give better results. The aim of this study was to examine the efficacy and safety of endoscopic hemoclips therapy and to evaluate potential benefits of this therapy combined with epinephrine in the treatment of bleeding peptic ulcers. Methods. This prospective randomized study included 70 patients with bleeding gastric or duodenal ulcer. In 34 of the patients endoscopic hemoclips therapy was applied (group I), and in 36 of them a combined therapy of hemoclips and epinephrine (group II). Results. Initial hemostasis was achieved in most patients treated with endoscopic hemoclips therapy (94.1%) as well as in the patients treated with combination therapy (97.2%). After initial hemostasis achieved rebleeding occurred in 3 (9.3%) patients treated with hemoclips and in 2 (5.7%) patients treated with combination therapy, but this difference was not statistically significant (p > 0.05). The difference in the achieved final hemostasis between the group I (91.1%) and the group II (94.4%) was not statistically significant. Also, the differences between the two groups of patients in the need for blood transfusions, length of hospital stay, need for surgery and mortality were not statistically significant (p > 0.05). Conclusion. Endoscopic hemoclips therapy is effective and safe in treatment of bleeding peptic ulcers. Combination therapy of hemoclips and epinephrine has no advantage over hemoclips monotherapy.